MED’s Position Paper on Digital Technology and the Copyright Act: Legislation without a Solution? - Nebel, Jens U (Victoria University of Wellington Law Review, 2005)
Courts in various jurisdictions have had to deal with the question of whether Internet Service Providers (ISPs) can be held liable for infringing acts committed by their subscribers. It is perhaps the most controversial legal issue emerging in the digital environment. Although New Zealand courts have yet to deal with the issue of ISP liability for copyright infringement, the Ministry of Economic Development (MED) has suggested a statutory solution for this apparent problem, which was put down in the 2002 Digital Technology and the Copyright Act 1994 Position Paper. In the Position Paper, MED proposes to exempt ISPs from liability for primary and secondary infringement under certain requirements. The suggested amendment to the Copyright Act 1994 raises several issues and questions, which will be addressed in this paper. The author argues that a total liability exemption fails to take all relevant policy factors into account and favours ISPs unilaterally. The paper suggests that ISPs do not need an exemption clause, because New Zealand’s copyright law, although full of uncertainties, appears to be relatively narrow compared to other jurisdictions. The proposed reform causes more problems than it addresses. The constructive knowledge standard, which ISPs have to meet in order to fall under the liability exemption clauses, is difficult to determine and amplifies the existing uncertainties. The author suggests that instead of curing the symptoms, the legislator should get at the root of the problems, which is the cluttered secondary infringement provisions and the nebulous concept of authorisation, which is the true reason for the legal uncertainty copyright owners and ISPs are currently facing.